2017
DOI: 10.18632/oncotarget.23484
|View full text |Cite
|
Sign up to set email alerts
|

The expression of circRNAs as a promising biomarker in the diagnosis and prognosis of human cancers: a systematic review and meta-analysis

Abstract: BackgroundCircRNAs, a type of non-coding RNAs with special loop structure, of which the aberrant expression is closely related to tumor growth, proliferation, metastasis and recurrence. It remains unclear whether they have the potential to be biomarkers for diagnosis and prognosis of cancers. The study aims to clarify the relationship of circRNAs expression with cancers diagnosis and prognosis.Materials and MethodsSensitivity, specificity, area under curve (AUC) and receiver operating characteristic curve (ROC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
31
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 52 publications
0
31
0
Order By: Relevance
“…Currently, studies have found that circRNAs are closely related to the prognosis of some human malignant tumors and involved in several tumors progression. 17,18 This paper demonstrated that hsa_circ_0087862 was significantly up-regulated in NSCLC. High hsa_circ_0087862 expression was prominently associated with poor outcome of NSCLC patients.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Currently, studies have found that circRNAs are closely related to the prognosis of some human malignant tumors and involved in several tumors progression. 17,18 This paper demonstrated that hsa_circ_0087862 was significantly up-regulated in NSCLC. High hsa_circ_0087862 expression was prominently associated with poor outcome of NSCLC patients.…”
Section: Discussionmentioning
confidence: 82%
“…This is significantly correlated with clinical manifestations such as tumor occurrence, stage and distant metastasis. 17,19 circRNAs are expected to become new tumor markers and therapeutic targets for human tumors. Data from this research illustrated that miR-1253 was tumor suppressor gene in NSCLC and its expression was down-regulated by hsa_circ_0087862.…”
Section: Discussionmentioning
confidence: 99%
“…During the computerized study search, we found two previous meta‐analysis by Wang et al and Ding et al that detected the association between circRNAs and cancer. A great many differences existed among these studies.…”
Section: Discussionmentioning
confidence: 99%
“…In previous meta-analysis, only five meta-analysis [32][33][34][35][36] detected the association between the circRNAs and carcinoma. However, in the studies of wang et al, Chen et al and Li et al [32,33,34], only one study was included to investigate the relationship between the circRNAs and CRC.…”
Section: Discussionmentioning
confidence: 99%
“…However, in the studies of wang et al, Chen et al and Li et al [32,33,34], only one study was included to investigate the relationship between the circRNAs and CRC. Li et al and Ding et al [35,36] assessed the diagnosis value of circRNAs for human cancers, in which five articles were included to investigate the diagnostic value of circRNAs for CRC, whereas they failed to discuss the role of circRNAs for CRC patients. In the present study, we collected all the relevant articles published to date and performed the meta-analysis including nineteen articles in 1307 CRC patients.…”
Section: Discussionmentioning
confidence: 99%